PERSEPSI WISATAWAN POLANDIA TERHADAP KUALITAS PELAYANAN AIRPORT REPRESENTATIVE PANORAMA DESTINATION BALI - Yulio Fernando; Dewa Gede Ngurah Byomantara; Putu Surya Laksana Rahjasa (J-TRUE: Journal of Travel and Leisure, 2024)
This research contains one main question, namely how Polish tourists perceive the service quality of Panorama Destination Bali's representative airport. Furthermore, the aim of this research is to determine the perceptions of Polish tourists regarding the quality of presentation airport services at Panorama Destination Bali. The method used in this research is quantitative descriptive. The data collection technique was carried out through observation with a sample of 100 respondents. Data collection was carried out by distributing questionnaires offline using a Google form, which then created a quick response code (QR) on the Google form. The results of the research show that the results of descriptive analysis testing regarding tourists' perceptions of the service quality of Airport Representative Panorama Destination Bali are included in the good category, this shows that Airport Representative Panorama Destination Bali is able to provide good service to tourists.